Pharmacokinetic Evaluation of Oral Viscous Budesonide in Paediatric Patients with Eosinophilic Oesophagitis in Repaired Oesophageal Atresia - Raffaele Simeoli; Sebastiano A. G. Lava; Alessandro Di Deo; Marco Roversi; Sara Cairoli; Renato Tambucci; Francesca Rea; Monica Malamisura; Giulia Angelino; Isabella Biondi; Alessandra Simonetti; Paola De Angelis; et al. (MDPI AG, 2024)
Eosinophilic oesophagitis is a long-term complication of oesophageal atresia (EA), an uncommon condition that affects approximately 1 in 3500 infants. An exploratory, open-label phase 2 clinical trial was conducted in paediatric eosinophilic oesophagitis after oesophageal atresia (EoE-EA) to assess the safety, pharmacokinetics, and efficacy of oral viscous budesonide (OVB). In total, eight patients were enrolled in the study and assigned to a twice-daily dosing regimen of either 0.8 or 1 mg OVB, depending on age and height, administered for 12 weeks. OVB was safe and effective in the treatment of EoE-EA. The current investigation focuses on the pharmacokinetics of budesonide and the impact of an oral viscous formulation on its absorption and bioavailability. Using a non-linear mixed effects approach, two distinct absorption profiles were identified, despite marked interindividual variability in drug concentrations. Budesonide exposure was higher than previously reported in children following oral inhalation. Even though no significant effect has been observed on serum cortisol levels, future studies should consider exploring different doses, schedules, and/or treatment durations, as there may be an opportunity to reduce the risk of cortisol suppression.